Monoclonal antibody against transforming growth factor Beta 1 does not influence liver regeneration after resection in large animal experiments - Bruha, Jan; Vycital, Ondrej; Tonar, Zbynek; Mirka, Hynek; Haidingerova, Lenka; Benes, Jan; Palek, Richard; Skala, Martin; Treska, Vladislav; Liska, Vaclav (In vivo (Athens, Greece), 2015)
BACKGROUND: Steatohepatitis is a type of histopathological liver injury that can be caused by chemotherapy [chemotherapy-associated steatohepatitis (CASH)] and can progress to liver fibrosis or cirrhosis. CASH impairs liver functions, including liver regeneration. Impaired liver regeneration reduces the number of patients who can undergo liver resection and reduces opportunities for curative therapies. Transforming growth factor-beta (TGFβ) is a potent mitotic inhibitor that participates during the last phase of liver regeneration. TGFβ has been studied as a potential solution to the development of liver fibrosis or hepatocellular carcinoma. AIM: The first aim of our study was to establish a large animal model of toxic liver injury and test the ability of a monoclonal antibody against TGFβ (MAB-TGFβ) to increase liver-regeneration capacity. The second aim was to evaluate the degree to which early preoperative administration of MAB-TGFβ influenced hepatic parenchyma regeneration following healthy liver resection in a swine experimental model. MATERIALS AND METHODS: Toxic liver injury was induced by alcohol consumption and regular intraperitoneal administration of carbon tetrachloride (CCl4) to piglets for 10 weeks. After 10 weeks, the piglets underwent liver resection of the left lateral and left medial liver lobes. Twenty-four hours after liver resection, MAB-TGFβ was administered to the experimental group (10 piglets) and a physiological solution to the control group (10 piglets) through an implemented port-a-cath. In the second part of the study, either MAB-TGFβ or a saline solution control were administered at 12 and 4 days prior to resection of the right lobes of healthy liver (six experimental and 10 control group subjects). Observation and follow-up was performed throughout the entire experiment. Ultrasound and biochemical tests (for albumin, cholinesterase, aspartate aminotransferase, alanine aminotransferase, γ-glutamyltransferase, alkaline phosphatase, bilirubin, urea, creatinine and ammonia levels) were performed on postoperative days 1, 3, 7, 10 and 14. A histopathological examination was performed after sacrificing the animals on the 14th postoperative day. RESULTS: No significant differences were observed between groups when using ultrasound volumetry to assess the regenerative volume of the liver in both experiments. The only significant differences found when comparing biochemical parameters between groups were higher serum levels of both creatinine and γ-glutamyl transferase in the experimental group with preoperative administration of MAB-TGFβ. There were no differences in the histological analyses of hepatic lobule cross-sectional area nor in the proliferative index between animals receiving MAB-TGFβ and those treated with physiological saline solution before resection. Hepatocytic cross-sectional areas were larger in animals treated with physiological solution versus those treated with MAB-TGFβ on the operative day; however, these values were comparable between groups by 14 days following resection. CONCLUSION: We established a large animal model of toxic liver injury that is comparable with CASH. The toxic injury that was induced without pause between administrations was probably more extensive than occurs in CASH, and there was no effect of MAB-TGFβ administration on liver regeneration. MAB-TGFβ administration did not lead to any observable side-effects, indicating that it could be a promising solution for use as an oncologic-targeted treatment.
Keywords: hepatocyty; Transforming growth factor beta; monoklonální protilátky; Sus scrofa; porcine animal model liver regeneration; lékové postižení jater; chemotherapy-associated steatohepatitis (CASH); velikost buňky; chlorid uhličitý; monoclonal antibody; transformující růstový faktor beta1; MAB-TGFβ; Hepatocytes; regenerace jater; Transforming Growth Factor beta1; Animals; Hepatectomy; játra; zvířata; Ethanol; ethanol; Antibodies, Monoclonal; Liver; Carbon Tetrachloride; Liver Regeneration; hepatektomie; Chemical and Drug Induced Liver Injury; Cell Size